Women's body mass index and oral administration of Misoprostol for induction of labor – A retrospective cohort study. Issue 5 (September 2021) - Helmig, Rikke Bek; Brogaard, Lise; Hvidman, Lone
Abstract: Pregnant women who are obese are at greater risk of pregnancy complications, including preeclampsia, gestational diabetes, and macrosomia, leading to an increased likelihood of induced labor. Little is known about pregnant women with obesity and the dose of Misoprostol needed for induction of labor (IOL). To investigate whether the cumulative dose of Misoprostol needed for induction of labor (IOL) is associated with women's body mass index (BMI), we conducted a retrospective study of the use of oral Misoprostol for IOL at the Department of Obstetrics and Gynecology, Aarhus University Hospital – a tertiary referral delivery unit with 4800 deliveries a year. Data on IOL among 1637 women with singleton pregnancies was collected in the period January 1st, 2014, to October 4th, 2017. Low-risk women were induced in an outpatient setting. Primary outcomes were Misoprostol dose, time between start of induction (first dose of Angusta®) and completed delivery, and mode of delivery. Secondary outcomes were neonatal data as Apgar score and pH of the umbilical artery. In this study, we found the total dose of Misoprostol needed for induction increased significantly with increasing BMI (p < 0.005). The time to delivery and the risk of Cesarean section increased with rising BMI class. However, 76% of inductions among the women with obesity ended in a vaginal delivery. For the neonatal outcomes, a total of 16 children had an Apgar score below 7 at five minutes and 14 had a pH less than 7.0; none of these results differed significantly between BMI classes. The perinatal and maternal mortality rate was 0%.